PERAN ORIENTASI KEWIRAUSAHAAN DALAM MENCIPTAKAN KINERJA BISNIS - Mulyanto, Kukuh (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2014)
Entrepeneurship orientation has been acknowledged in literature and practice as a vital element of economic and organizational growth, success and competitiveness and can be considered as a unique competitive advantage. The purpose of the paper is to provide a comprehensive analysis of the concept of entrepeneurship orientation. Concluding, the paper suggests directions for future research.